Use of FLOSEAL® as a scaffold and its impact on induced neural stem cell phenotype, persistence, and efficacy. Issue 2 (21st January 2022) - Bomba, Hunter N.; Carey‐Ewend, Abigail; Sheets, Kevin T.; Valdivia, Alain; Goetz, Morgan; Findlay, Ingrid A.; Mercer‐Smith, Alison; Kass, Lauren E.; Khagi, Simon; Hingtgen, Shawn D.
Abstract: Induced neural stem cells (iNSCs) have emerged as a promising therapeutic platform for glioblastoma (GBM). iNSCs have the innate ability to home to tumor foci, making them ideal carriers for antitumor payloads. However, the in vivo persistence of iNSCs limits their therapeutic potential. We hypothesized that by encapsulating iNSCs in the FDA‐approved, hemostatic matrix FLOSEAL®, we could increase their persistence and, as a result, therapeutic durability. Encapsulated iNSCs persisted for 95 days, whereas iNSCs injected into the brain parenchyma persisted only 2 weeks in mice. Two orthotopic GBM tumor models were used to test the efficacy of encapsulated iNSCs. In the GBM8 tumor model, mice that received therapeutic iNSCs encapsulated in FLOSEAL® survived 30 to 60 days longer than mice that received nonencapsulated cells. However, the U87 tumor model showed no significant differences in survival between these two groups, likely due to the more solid and dense nature of the tumor. Interestingly, the interaction of iNSCs with FLOSEAL® appears to downregulate some markers of proliferation, anti‐apoptosis, migration, and therapy which could also play a role in treatment efficacy and durability. Our results demonstrate that while FLOSEAL® significantly improves iNSC persistence, this alone is insufficient to enhance therapeutic durability.